Prion diseases - Gambetti, Pierluigi (Henry Stewart Talks, 2007)
Normal function of prion protein, Prion diseases, Mechanism of propagation of PrP, Propagation in acquired and familial forms, Pathogenic hypothesis, Human pathogenic mutation and polymorphisms, Laboratory methods, Epidemiology, Sporadic prion diseases, New variant CJD, Treatment of prion disease
Archived at 2020/08/13